Financial Resource Provision and Utilization in Education: as Perceived by Teachers and Principals’ in Secondary Schools - Elegonye, Miriam Olucbi; Daudu , Yahaya; Tayo , Adedayo Ayinde (International Journal of Educational Management, 2025)
Abstract The study examines the financial resource provision and utilization in education: as perceived by teachers and principals’ in secondary school in Zaria and Giwa Education zones, Kaduna state. Two objectives and two research questions guided the study. A descriptive survey research design was adopted for this study and a random sampling technique was used in selecting 628 respondents from a population of 2092. Ten items in a structured questionnaire with the use of five (5) Likert scale of strongly Agreed, Agreed, Undecided, Disagreed and strongly disagreed was adopted to collect data from participants. The Weighted mean of 3. O was used as the bench mark to determine the acceptability or other wise of the response of the respondents. Findings from the study showed that PTA is paid promptly in the school. Also, School fees are not paid regularly as at when due. Also, the study shows that Principals always participate in financial budgeting, fees and other levies are managed by the principal in the school. Based on the findings and conclusions of the study it was recommended among others that the Government and school authorities should make adequate annual budgetary provisions for school funds to allow for periodic replacement, continuity and availability. State government should increase the financial resources allocated to schools.